Caracterização do perfil de inovação dos setores industriais do complexo econômico industrial da saúde: discussão da política tecnológica, inovação e comércio exterior - Cavalcante, Jupiraci Barros (2013)
Compared to developed countries, Brazil is relatively distant from the results of innovation. The Brazilian position although has made a significant improvement, going from seventy-two place to sixty-four place, continues with the weakened position mainly in three indices: evalu-ation of institutions (political environment, regulatory and business), redit and R & D. when it refers to the innovation process, bottlenecks are related not only to the high-tech sector, but the majority of economic activities, since the pattern of production in Brazil is still essentially primary. The segment of high technological complexity for decades was marked by visible distortions in the trade balance, resulting in continual trade deficit condition. The same condi-tion occurred in the productive segment of Industrial health (Pharmaceutical and EMHO seg-ment) Economic Complex. Commercial fragility of CEIS between 2000 and 2010 was due to two logics: the productive, structural logic and low investment in innovation indicators as-sessed by the PINTEC (Research on Technological Innovation). The foreign trade of the CEIS showed high participation of imports in the value of industrial transformation industrial, while the share of exports was small, although the sectors increase the volume of exports from 2004. The survey through of the analysis ordinal Spearman the performance was associated CEIS with total expenditures on health and federal health expenditures in the share of domes-tic production (in GDP). The export performance of pharmaceutical sector was positively as-sociated with increased rates of international patent classification in area of pharmaceutical sciences. In relation to capacity innovative the PINTEC indicators point to the need to strengthen the industrial base through innovation, of increased training expenditures, spending on procurement of external expertise in research and development, and increase the rate of introduction of innovations aimed at the domestic market and expand cooperative relations. All this emerges from the understanding of sector dynamics of innovation, sectoral policies and guidelines planned in view of the dynamic nature of competitiveness.